THE IMPLEMENTATION OF INDONESIA HEALTH MINISTER REGULATION RELATED TO STERILIZED DISPENSING IN "X" HOSPITAL IN GIANYAR-BALI - Dewi, Ni Luh Putu Lestari; Ginarsih, Ni Made Ari; Wirasuta, I Made Agus Gelgel (Journal Pharmaceutical Science and Application; Vol 3 No 2 (2021): Journal Pharmaceutical Science and Application, 2021)
Background: The application of Regulation of the Minister of Health Number 72 of 2016 is very important to be implemented in every Pharmacy Installation in a hospital, one of which is in the clinical pharmacy service section, namely dispensing sterile preparations to avoid the possibility of medication errors. Objective: The research aimed to find out how the implementation of Regulation of the Minister of Health Number 72 of 2016 stipulated in the basic guidelines of aseptic techniques related to space, equipment, and the implementation of dispensing sterile preparations with its practice in Hospital "X" Gianyar, Bali. Methods: This research used Sequential Explanatory design by combining quantitative and qualitative methods. Results: The results of quantitative research with a checklist found the percentage of completeness of the room and equipment by 100%, while the conformity of the practice with the guidelines of 76.48% is appropriate. The results of qualitative research with triangulation matrices that practice is by the guidelines. Conclusion: Dispensing sterile preparations at the Hospital "X" is following the basic guidelines of aseptic techniques that refer to Regulation of the Minister of Health Number 72 of 2016. Keywords: Implementation, regulation, dispensing, sterile preparations, guidelines, medication errors